Personality and life satisfaction: incremental validity of the Dark Triad over the Big Five - Wertag, Anja (Array, 2014)
Personality traits are documented as one of the best predictors of subjective well-being. While the relation between some personality traits and life satisfaction has been intensively investigated, research regarding some is still scarce. Therefore, the aim of this study was to investigate the relationship between life satisfaction and the Dark Triad, as well as the incremental validity of the Dark Triad traits over the Big Five personality traits in predicting life satisfaction. Satisfaction with life scale (SWLS, Diener et al., 1985), IPIP (Mlačić & Goldberg, 2007) and Short Dark Triad scale (SD3-28 ; Paulhus & Johnes, 2011) were administered to 626 students (250 male) from various faculties of University of Zagreb within a larger study. Results of hierarchical regressions showed that, after controlling for age and gender, the Big Five accounted for unique 12.6% variance of life satisfaction, while the Dark Triad had only marginal incremental validity over the Big Five.